Reynolds number scaling to predict droplet size distribution in dispersed and undispersed subsurface oil releases. Issue 1 (15th December 2016) - Li, Pu; Weng, Linlu; Niu, Haibo; Robinson, Brian; King, Thomas; Conmy, Robyn; Lee, Kenneth; Liu, Lei
Abstract: This study was aimed at testing the applicability of modified Weber number scaling with Alaska North Slope (ANS) crude oil, and developing a Reynolds number scaling approach for oil droplet size prediction for high viscosity oils. Dispersant to oil ratio and empirical coefficients were also quantified. Finally, a two-step Rosin-Rammler scheme was introduced for the determination of droplet size distribution. This new approach appeared more advantageous in avoiding the inconsistency in interfacial tension measurements, and consequently delivered concise droplet size prediction. Calculated and observed data correlated well based on Reynolds number scaling. The relation indicated that chemical dispersant played an important role in reducing the droplet size of ANS under different seasonal conditions. The proposed Reynolds number scaling and two-step Rosin-Rammler approaches provide a concise, reliable way to predict droplet size distribution, supporting decision making in chemical dispersant application during an offshore oil spill. Highlights: Modified Weber number scaling was tested with a high viscosity crude oil. A Reynolds number scaling approach was introduced for general droplet size prediction. The relationship between dispersant to oil ratio and oil droplet size was quantified. A more accurate approach was provided to determine the oil droplet size distribution. These approaches effectively support dispersant applications in oil spill response.